Crucial Dimensions of Human Altruism. Affective vs. Conceptual Factors Leading to Helping or Reinforcing Others - Szuster, Anna (Frontiers in Psychology, 2016)
The aim of this article is to identify factors leading to favorable attitudes toward other people from different social categories. The parts of article reflect diverse levels of altruism regulation from primary affective responses to the environment, through social norms, to abstract moral concepts related to good and evil. The latter allow understanding of the perspective of other people (including those belonging to out-groups), acceptance of their values and engagement not only in helping behavior but also in supporting the development of others.